(untitled) (Journal of Analytical Oncology, 2021)
Background: Intensity-modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC) acts on the tumor and affects surrounding organs at risk (OARs). This study aimed to quantify the geometric changes in the parotid gland, the submandibular gland (SMG), and the thyroid, during the course of treatment. Methods: Twenty patients diagnosed with locally advanced NPC were consecutively enrolled, and received definitive chemoradiotherapy in 33 fractions over 6.5 weeks. Each patient underwent planning computed tomography (pCT) followed by six weekly repeat CTs (rCTs) without contrast enhancement. Each rCT was rigidly registered to its pCT. Changes in terms of volume, position, and shape of the OARs were assessed. Differences in left- and right-sided OARs were compared. Results: Radiation doses to the parotid, SMG, and thyroid were 32.12 ± 11.2 Gy (mean ± standard deviation SD), 25.46 ± 8.62 Gy, and 18.89 ± 10.24 Gy, respectively. Volume reductions of 28.6% ± 14.6% (mean ± SD), 26.6% ± 17.1%, and 12.3% ± 11.3% were observed in the parotid, SMG, and thyroid, respectively. Rate of volume loss for the parotid and SMG decreased from 1.6-1.7% per day in the first week to 0.5%-0.6% in the last week. Contrarily, not all thyroid lobes decreased in volume during treatment. The center of mass of the parotid shifted 2.0-2.6 mm medially; for the SMG and thyroid, a 0.1-0.5 mm medial shift was noted. The displacement in the anterior-posterior and cranial-caudal directions was < 0.6 mm. The 3-dimensional vector displacements of the parotid and SMG were 2.2-2.9 mm, and that of thyroid was 4.0-4.3 mm. The overlapping metrics of all three OARs decreased over time, and the shortest perpendicular distance increased from 1.5-1.8 mm in the first week to 2.4-2.5 mm in the last week. The geometric differences between weeks were statistically significant (P<0.05). Conclusions: The volume, position, and shape of the OARs changed significantly during IMRT for NPC. These geometric changes displayed a time association, suggesting the necessity to re-plan treatment for better sparing of these OARs.